2020
DOI: 10.1155/2020/2723705
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology Identifies the Mechanisms of Action of Tongxie Anchang Decoction in the Treatment of Irritable Bowel Syndrome with Diarrhea Predominant

Abstract: Aim. This study aims to uncover the pharmacological mechanism of Tongxie Anchang Decoction (TXACD), a new and effective traditional Chinese medicine (TCM) prescription, for treating irritable bowel syndrome with diarrhea predominant (IBS-D) using network pharmacology. Methods. The active compounds and putative targets of TXACD were retrieved from TCMSP database and published literature; related target genes of IBS-D were retrieved from GeneCards; PPI network of the common target hub gene was constructed by STR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…And the results reported that the flavored Tongxie Yaofang had a significant effect on the symptoms of patients with IBS-D[ 117 ], and improving the gut microbiome, alleviating visceral hypersensitivity, regulating 5-HT level in patients, and inhibiting colonic contraction are mechanisms for the treatment of IBS[ 118 - 120 ]. Moreover, Tongxie Anchang Decoction improves IBS by reducing visceral hypersensitivity, reversing mast cell infiltration, and regulating 5-HT[ 118 , 121 ]. And Xiang Sha Liu Jun Zi Decoction reduced the mean diarrhea score of IBS patients[ 122 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…And the results reported that the flavored Tongxie Yaofang had a significant effect on the symptoms of patients with IBS-D[ 117 ], and improving the gut microbiome, alleviating visceral hypersensitivity, regulating 5-HT level in patients, and inhibiting colonic contraction are mechanisms for the treatment of IBS[ 118 - 120 ]. Moreover, Tongxie Anchang Decoction improves IBS by reducing visceral hypersensitivity, reversing mast cell infiltration, and regulating 5-HT[ 118 , 121 ]. And Xiang Sha Liu Jun Zi Decoction reduced the mean diarrhea score of IBS patients[ 122 ].…”
Section: Treatmentsmentioning
confidence: 99%